Pengaruh Commmunity of Inquiry terhadap Student’s Satisfaction in Online Learning di Universitas Islam Bandung - Puri Luthfiarini; Susandari (Bandung Conference Series: Psychology Science, 2022)
Abstract. E-learning implementation during Pandemic covid-19, students experienced dissatisfaction towards the significance of learning attendance, social relationship, and comprehension. This phenomenon indicates problems with the perception of Community of Inquiry which consists of Teaching Presence, Social Presence, and Cognitive Presence that has effects on student's online learning unsatisfactory. This study aims to find out the Impact of Community of Inquiry toward Student's Satisfaction Online Learning in Universitas Islam Bandung. The instruments used are Community of Inquiry from Shea & Bidjerano (2010), and Students Satisfaction Online Learning from Dziuban (2015). The sampling used in this study is Cluster random sampling, taking 377 students from Social study fields. This study used multiple linier regression method. Results shows that Community of Inquiry has a significant impact on Students Satisfaction Online Learning up to 44.3% with 0.003 signification score. The majority of students (56.23%) perceives Teaching Presence as "quite good" and 54.91% perceives Social presence as "quite good". Then in Cognitive Presence, the majority of students (84.35%) are on the Exploration phase. Social presence is the most impactful dimension on Students Satisfaction Online Learning in Universitas Islam Bandung. Abstrak. Dalam pelaksanaan e-learning di masa pandemi ini, Mahasiswa Unisba mengalami ketidakpuasan dalam pemaknaan kehadiran pengajaran, hubungan sosial, dan pemahaman. Fenomena ini menunjukkan masalah dalam persepsi Community of Inquiry yang terdiri dari Teaching Presence, Social Presence, dan Cognitive Presence yang memiliki pengaruh terhadap kepuasan mahasiswa mengenai pembelajaran online. Tujuan penelitian ini adalah untuk melihat pengaruh dari Community of Inquiry terhadap Students Satisfaction Online Learning di Universitas Islam Bandung. Alat Ukur Community of Inquiry menggunakan instrument dari Shea&Bidjerano (2010), dan alat ukur Students Satisfaction Online Learning dari Dziuban (2015). Adapun penetapan sampel penelitian menggunakan Cluster random sampling, diambil dari program studi dengan rumpun ilmu sosial sebanyak 377 mahasiswa. Metode menggunakan regresi linear berganda. Berdasarkan hasil regresi, ditemukan bahwa Community of Inquiry memiliki kontribusi dan signifikan terhadap Students Satisfaction Online Learning sebesar 44,3% dengan nilai signifikansi 0,003. Mayoritas mahasiswa (56,23%) mempersepsikan Teaching Presence tergolong cukup baik dan 54,91% mahasiswa mempersepsikan Social Presence tergolong cukup baik. Sedangkan dalam Cognitive Presence, mayoritas mahasiswa (84,35%) tergolong berada di tahap Exploration. Social Presence merupakan dimensi yang paling berkontribusi terhadap Students Satisfaction Online Learning di Universitas Islam Bandung.